Конвертирование авиационных и корабельных газотурбинных двигателей в стационарные установки промышленного назначения - Коваль, Вячеслав Алексеевич; Ануров, Ю. М.; Нагога, Г. П.; Романов, В. В.; Валюхов, С. Г. (Eastern-European Journal of Enterprise Technologies, 2009)
The summary of the book (in two parts), devoted is presented to converting aviation and ship gas-turbine engines to stationary installations for development of the electric power and swapping of gas. In the first part it is considered thermodynamics designing gas-turbine the engine including the three-dimensional analysis of a stream in basic elements of the machine. The second part contains data concerning methods of increase in a resource and an estimation of parameters of reliability of stationary installations, and also about methods of their calculation The book is intended for experts in the field of gas-turbo plant, and also for students and post-graduate students of corresponding specialties of higher educational institutions